Environmental gradients shape genetic variation in the desert moss, Syntrichia caninervis Mitt. (Pottiaceae) - Ugbad A. Farah; Kirsten M. Fisher (Scientific Reports)
Abstract The moss Syntrichia caninervis Mitt. is distributed throughout drylands globally, and often anchors ecologically significant communities known as biological soil crusts (biocrusts). The species occupies a variety of dryland habitats with varying levels of drought and temperature stress, suggesting the potential for ecological specialization within S. caninervis. Here, we sampled S. caninervis from sites along two elevation gradients and used restriction site associated DNA sequencing to compare the relative impacts of environmental factors and geospatial distances on genetic differentiation in S. caninervis populations. While we found no evidence of isolation by distance in our data, one environmental variable, mean annual precipitation (MAP), was found to be a positive predictor of FST. An ecological association analysis identified 32 SNP alleles that covary significantly with MAP, 15 of which fall within the exonic regions of genes with annotations suggesting diverse roles in response to dehydration stress. Understanding the degree to which genetic variation in S. caninervis is associated with environmental factors is key to predicting its potential for persistence in the face of global climate change, which is predicted to be especially detrimental to desert organisms already living at their physiological limits.